2016
DOI: 10.1155/2016/7414737
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Multiple Pour Cast from Various Elastomer Impression Methods

Abstract: The accurate duplicate cast obtained from a single impression reduces the profession clinical time, patient inconvenience, and extra material cost. The stainless steel working cast model assembly consisting of two abutments and one pontic area was fabricated. Two sets of six each custom aluminum trays were fabricated, with five mm spacer and two mm spacer. The impression methods evaluated during the study were additional silicone putty reline (two steps), heavy-light body (one step), monophase (one step), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…It was previously reported that the two-step technique with uniform spacer had the slightest dimensional changes compared to other impression techniques. [ 18 19 ] If a layer of moderate thickness is uniformly distributed, the overall constant deformation of the silicone impression materials would be ignorable. [ 20 ] Furthermore, using impression materials of different consistencies and applying them in multistep procedures would help recording the most delicate details of the original.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that the two-step technique with uniform spacer had the slightest dimensional changes compared to other impression techniques. [ 18 19 ] If a layer of moderate thickness is uniformly distributed, the overall constant deformation of the silicone impression materials would be ignorable. [ 20 ] Furthermore, using impression materials of different consistencies and applying them in multistep procedures would help recording the most delicate details of the original.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the use of these materials presents the risk of distortion, expansion, or shrinkage due to numerous steps involved. Additionally, they need large storage spaces and there is a risk of damage during time [15,16].…”
Section: Introductionmentioning
confidence: 99%